South Korea's Green Revolution : the story of T'ongil - Lee, Livia Yu Ting (Nanyang Technological University, 2022)
In 1978, South Korea announced the success of its Green Revolution. Central to this success was the high-yielding variety (HYV), T’ongil. At the same time, the name T’ongil directly expresses the reunification of the Korean peninsula. How do we then make sense of the creation of this HYV especially in the backdrop of the Cold War? More importantly, what set the global Green Revolution apart from South Korea’s Green Revolution? This paper will hence explore the broader political context in which T’ongil was created. Analysis of T’ongil through the 1970s to 1990s reveal the changing perceptions of the new variety; what had once been a celebrated success by the Park Chung Hee administration met with rapid decline throughout the 1980s and 1990s. Even during the 1970s, there were varying definitions of success: self-sufficiency for Park, taste and durability for Mun-Heu Hue and positive reception of farmers. On the onset of post-Cold War and globalisation, T’ongil came to represent globalisation and evolving inter-Korean relations. Hence, this paper argues that T’ongil was a site of contestation amongst various actors who held different perceptions based on their circumstances.